2021
DOI: 10.33910/2687-153x-2021-2-3-115-121
|View full text |Cite
|
Sign up to set email alerts
|

Effect of doping of molybdenum on the optical properties of glasses of the As—S system

Abstract: This article discusses the spectral dependences of the absorption coefficient of thin arsenic sulphide films obtained by spin-coating, identified using a single-beam spectrophotometer in the wavelength range of 400-1000 nm. The effect of doping of molybdenum on the optical band gap is studied. While for a pure glass the band gap decreases with higher sulphur concentration, the opposite trend is observed in glass doped with molybdenum. Molybdenum doping also leads to an increase in Urbach energy. The obtained e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
(10 reference statements)
0
1
0
Order By: Relevance
“…As the studies performed earlier (Provotorov et al 2021) show, the observed shape of the optical transmission spectra T(λ) (T is the transmittance, λ is the radiation wavelength) of samples of ChGS films is characteristic of the films of the system under study. It has been established that in the transparency region this spectral dependence is significantly distorted by interference phenomena in thin films due to multiple reflections of the incident radiation, which, in turn, may indicate the homogeneity of the synthesized film.…”
Section: Resultsmentioning
confidence: 66%
“…As the studies performed earlier (Provotorov et al 2021) show, the observed shape of the optical transmission spectra T(λ) (T is the transmittance, λ is the radiation wavelength) of samples of ChGS films is characteristic of the films of the system under study. It has been established that in the transparency region this spectral dependence is significantly distorted by interference phenomena in thin films due to multiple reflections of the incident radiation, which, in turn, may indicate the homogeneity of the synthesized film.…”
Section: Resultsmentioning
confidence: 66%